2019
DOI: 10.3390/microorganisms7110576
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeny of Anoxygenic Photosynthesis Based on Sequences of Photosynthetic Reaction Center Proteins and a Key Enzyme in Bacteriochlorophyll Biosynthesis, the Chlorophyllide Reductase

Abstract: Photosynthesis is a key process for the establishment and maintenance of life on earth, and it is manifested in several major lineages of the prokaryote tree of life. The evolution of photosynthesis in anoxygenic photosynthetic bacteria is of major interest as these have the most ancient roots of photosynthetic systems. The phylogenetic relations between anoxygenic phototrophic bacteria were compared on the basis of sequences of key proteins of the type-II photosynthetic reaction center, including PufLM and Pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(50 citation statements)
references
References 42 publications
2
48
0
Order By: Relevance
“…Smaller numbers of the phylotypes were classified as members of Betaproteobacteria, Gemmatimonadetes, and unidentified phylogenetic groups. Phylotypes 12 and 16, assigned to Gemmatimonadetes and Betaproteobacteria, respectively, nested into the clade of Alphaproteobacteria, which can be explained by ancestral lateral transfer of a photosynthetic gene set with pufM from phototrophic alphaproteobacteria [57,59,60]. Except for the Gemmatimonadetes (phylotype 12), Dinoroseobacter (phylotype 15), and unidentified clones, all of the pufM clones detected could be assigned to members of PSB and PNSB.…”
Section: Pufm Gene Clone Phylotypingmentioning
confidence: 96%
“…Smaller numbers of the phylotypes were classified as members of Betaproteobacteria, Gemmatimonadetes, and unidentified phylogenetic groups. Phylotypes 12 and 16, assigned to Gemmatimonadetes and Betaproteobacteria, respectively, nested into the clade of Alphaproteobacteria, which can be explained by ancestral lateral transfer of a photosynthetic gene set with pufM from phototrophic alphaproteobacteria [57,59,60]. Except for the Gemmatimonadetes (phylotype 12), Dinoroseobacter (phylotype 15), and unidentified clones, all of the pufM clones detected could be assigned to members of PSB and PNSB.…”
Section: Pufm Gene Clone Phylotypingmentioning
confidence: 96%
“…Notably, both DPOR and COR are nitrogenase-like enzymes (Nomata et al 2006, Chew & Bryant 2007, Tsukatani et al 2013, and both were abundant in all metatranscriptomes and metagenomes. DPOR and COR were particularly common within the Limnohabitans and Polynucleobacter genera, as some strains of these abundant freshwater bacteria are capable of performing aerobic anoxygenic photosynthesis (Kasalický et al 2018, Imhoff et al 2019, Hahn et al 2017. DPOR exclusively was also found in several cyanobacterial groups-such as Pseudanabaena, Dolichospermum, Gloeomargarita and Oscillatoria-in the metatranscriptome data.…”
Section: Evidence For Methane Production By Cyanobacteria and Proteobmentioning
confidence: 92%
“…We found that phnJ genes commonly clustered with other phn genes on the same contigs, particularly those from the Comamonadaceae. For example, contigs >50 kb containing phnC, phnD, phnE, phnI, phnJ, phnK, phnL, phnM were present in metagenomes from the LG2 and L6 incubations, and were affiliated with the abundant freshwater bacterial group Limnohabitans (Newton et al 2011, Kasalický et al 2018, Imhoff et al 2019, as well as other members of the Comamonadaceae, such as Hydrogenophaga and Acidovorax. Several longer contigs also contained pst or pho genes involved in P uptake and metabolism.…”
Section: Methylphosphonate Breakdown As a Source Of Methanementioning
confidence: 99%
See 2 more Smart Citations